Association of Selected Fitness Variables with Perceived Performance Levels in Lawn Tennis Players - Manchanda, Sukriti; Saxena, Shobhit; Sharma, Pooja; Rizvi, Moattar Raza; Sharma, Ankita; Ahmad, Irshad; Kachanathu, Shaji John (Journal of Health and Allied Sciences NU, 2023)
Objectives Lawn tennis is an explosive sport that involves various fitness parameters such as explosive strength, endurance, power, and agility. Improved physical fitness leads to superior athletic performance. The coach's perception is contingent upon his perception of the player at the time the athlete is comparing himself to the coach. Thus, this study aimed to determine the association between chosen fitness factors and perceived performance by coach in lawn tennis players. Thus, the study aims to detect the relationship between different fitness variables and perceived level of performance in lawn tennis player.Materials and Methods Fifty-two lawn tennis players from two sports academies were measured for various parameters of fitness and perceived performance level as rated by the coach.Statistical Analysis The association between selected fitness metrics and perceived performance in lawn tennis players was investigated using Pearson's correlation test. Furthermore, the data were analyzed with paired t-test for male and female group, and ANOVA was used to analyze the difference between the levels of performance.Results Fatigue index, closed kinetic chain upper extremity stability (CKCUEST) test, and peak power and energy expenditure taken by metabolic equivalent (MET) calculation was found to be statistically different between males and females. While comparing BMI with the peak power, there was a weak positive correlation for males, while for female there was no correlation. Metabolic equivalent, energy expenditure, and peak power were positively correlated with the level of performance; however, fatigue index and level of performance had a negative nonsignificant correlation.Conclusion Peak power, fatigue index, energy expenditure, and BMI were found to be associated in males, but not in females. Peak power and energy expenditure were connected to performance in both genders.
Keywords: energy expenditure; fatigue index; peak power; upper limb stability; perceived performance